POST-GRUNIGIAN POLITICAL COMMUNICATION OF FEMALE DPD MEMBERS WITHOUT POLITICAL FAMILY BACKGROUND - M. Elfan Kaukab; Muhamad Agung Dharmajaya; Aminah Aminah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2026)
Flooding in rural areas remains a complex and ongoing environmental issue, particularly in regions where rivers flow through residential settlements. The decline in river function caused by sedimentation, channel narrowing, and the accumulation of domestic waste has become one of the main factors contributing to flooding. Bojong Loa Village, Cisoka District, Tangerang Regency, experiences these conditions due to low public awareness of environmental management and the lack of an integrated waste management system. This study aims to analyze the implementation of community empowerment programs in environmental management and river normalization as flood prevention efforts. The research employed a descriptive qualitative method with a participatory approach through field observations, environmental education, active community involvement, and post-activity evaluation. The results indicate that river normalization activities improved water flow capacity and reduced the potential for inundation, while environmental education programs contributed to changes in community behavior regarding waste management. This study concludes that collaborative and sustainable community empowerment is effective in improving environmental quality and reducing flood risk in rural areas.